PENGARUH ASIMETRI INFORMASI, MORALITAS DAN MOTIVASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Pransiska, Pransiska; Sari, Ati Retna; Made, Anwar (Jurnal Riset Mahasiswa Akuntansi, 2017)
ABSTRACT: This study aims to examine and explain: (1) the extent to which informationasymmetry influences the tendency of accounting fraud, (2) the extent to which morality influencesthe tendency of accounting fraud, (3) the extent to which motivation influences the tendency ofaccounting fraud and (4) the extent to which information asymmetry, morality and motivationinfluence the tendency of accounting fraud. The type of research data is primary data. Therespondents were staff at the Batu City Regional Finance Agency. The population in this studyamounted to 62 BKD staff. The sampling technique uses purposive sampling with a total sample of52 respondents. This study uses multiple linear regression analysis, validity test, reliability test,normality test, multicollinearity test and heteroscedasticity test. Based on the results of the study itcan be concluded that the information asymmetry, morality and motivation influence the tendencyof accounting fraud by 67.7% while the remaining 32.3% is influenced by other variables notexamined.